Effect of Exercise on Stress Urinary Incontinence in Women: A Review Study - Shiva Khodarahmi; Nourosadat Kariman; Abbas Ebadi; Giti Ozgoli (Mashhad University of Medical Sciences, 2018)
Introduction: Stress urinary incontinence is a disabling disease that affects the lives of women and requires solutions. Therefore, this study aimed to evaluate the effect of exercise on stress urinary incontinence in women. Methods: In this review study, information related to the effects of exercise on stress urinary incontinence in women were searched in Persian and English in the databases of clinical trials registry centers, including Elsevier, ProQuest, UpToDate, Scopus, Magiran, Irandoc, SID, Iran medex, Sciencedirect, Pubmed, GoogleScholar and web of science using keywords of urinary incontinence, stress urinary incontinence, exercise, and elderly and their Persian equivalents. The search was based on a mesh during 2000-2017. Results: In total, 23 interventional studies, including clinical trials and quasi-experiments, which were published during 2000-2017 and met the inclusion criteria, were assessed. In the review conducted on women with different age groups from across the world, most studies have reported a positive relationship between exercise and stress urinating incontinence. Conclusion: Based on the published studies, following exercises are effective in prevention and treatment of stress urinary incontinence in women: regular daily pelvic floor muscle exercises, co-contraction of the muscles of the pelvic floor and central trunk or transverse abdominal, gymnastics, Pilates, exercise of pelvic floor muscles along with biofeedback intravaginal or perineal, pelvic floor muscles training using a muscles shocking device or electrical stimulation, Valsalva, physical fitness, Paula's Exercise, Kegel Exercise, training of the gluteal and adductor thigh muscles, Tensberger's exercises, physiotherapy, isometric exercises, and exercise in water.